Autophagy regulates neuronal excitability by controlling cAMP/protein kinase A signaling at the synapse - Melina Overhoff; Frederik Tellkamp; Simon Heß; Marianna Tolve; Janine Tutas; Marcel Faerfers; Lotte Ickert; Milad Mohammadi; Elodie De Bruyckere; Emmanouela Kallergi; Andrea Delle Vedove; Vassiliki Nikoletopoulou; et al. (2022)
Abstract Autophagy provides nutrients during starvation and eliminates detrimental cellular components. However, accumulating evidence indicates that autophagy is not merely a housekeeping process. Here, by combining mouse models of neuron‐specific ATG5 deficiency in either excitatory or inhibitory neurons with quantitative proteomics, high‐content microscopy, and live‐imaging approaches, we show that autophagy protein ATG5 functions in neurons to regulate cAMP‐dependent protein kinase A (PKA)‐mediated phosphorylation of a synapse‐confined proteome. This function of ATG5 is independent of bulk turnover of synaptic proteins and requires the targeting of PKA inhibitory R1 subunits to autophagosomes. Neuronal loss of ATG5 causes synaptic accumulation of PKA‐R1, which sequesters the PKA catalytic subunit and diminishes cAMP/PKA‐dependent phosphorylation of postsynaptic cytoskeletal proteins that mediate AMPAR trafficking. Furthermore, ATG5 deletion in glutamatergic neurons augments AMPAR‐dependent excitatory neurotransmission and causes the appearance of spontaneous recurrent seizures in mice. Our findings identify a novel role of autophagy in regulating PKA signaling at glutamatergic synapses and suggest the PKA as a target for restoration of synaptic function in neurodegenerative conditions with autophagy dysfunction.